The relationship between knowledge management practices and staffs performance in CIMB principla asset management headquaters (HQ) / Farah Illyanie Omran - Omran, Farah Illyanie (2017)
Knowledge Management Practice is the set of management activities conducted in a firm with the aim of improving the effectiveness and efficiency of organizational knowledge resources. This research discussed on the relationship between knowledge management practices and staff performance. This knowledge practices becomes productive when combined staff performance as dependent variable. Practically, this research describes implementation of KMP expertise in staff performance in CIMB Principal Asset Management Headquarters, using the scientific method of knowledge acquisition, knowledge dissemination and knowledge utilization. The questionnaire has been adjusted to match the environment of this research and it was applied to a sample of about 137 staffs in CIMB Principal Asset Management Headquarters. It was found that knowledge management practices namely knowledge acquisition, knowledge dissemination and knowledge utilization have positive and significant relationship with staff performance